Dolomitization and Hypogenic Dissolution of the Eocene Avanah Formation, Iraqi Kurdistan - Qadir, Gazang H.; Mansurbeg, Howri (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This study constrains the mechanism of extensive dolomitization and its impact on reservoir quality of the shallowwater marine ramp carbonates of the Avanah Formation (Eocene), Iraqi Kurdistan. The presence of shoal deposits, which semiisolate a lagoon water body from the open marine, suggests that dolomitization was by seepage reflux of brines. Nevertheless, the absence of eogenetic gypsum/anhydrite in the dolostones succession indicates that the dolomitizing fluids were mesohaline/penesaline brines formed during cycles of relative sea level (RSL) fall. Dolomitization resulted in the formation of abundant intercrystalline and moldic/vuggy pores. Restriction of dolomitization and related reservoir quality improvement to the lower part of the formation is attributed to an overall 3rd order fall in the RSL. Conversely, the lack of dolomitization in the upper part of the formation is attributed to deposition during 3rd order marine transgression, which prevented severe restriction and evaporation of the inner ramp and, consequently, inhibited the development of dolomitizing brines. It is suggested that hypogenic dissolution (karstification) by upward flow of aggressive fluids along faults and fractures during the Zagros Orogeny caused dissolution and considerable porosity and permeability improvement of the dolostones. A greater extent of dolostones dissolution in the flanks, which was accompanied by calcite cementation, compared to the crest, reflects the role of oil emplacement in the retardation of diagenetic reactions.